From 70 thousand to 7 Million : integrated activation as a driver of sponsor and property reach - Pasqualicchio, Gary; O'Reilly, Norm; Elowson, Ed (London : Human Kinetics, Inc., 2017)
For years, sport properties and corporate sponsors have struggled to develop strategies to activate their expansive partnerships, particularly those without high-ranking national media coverage. This case analyzes a successful, multilayered sponsorship activation tied to the 2012 retirement of Philadelphia Eagles star Brian Dawkins. The Eagles, in partnership with AAA and Marvel, created and promoted a unique weekend around Dawkins' retirement that included a NASCAR race, an NFL Sunday Night Football Game, and a meet-and-greet with Dawkins; this weekend was marketed extensively across various modes of media. The partners' goals were to engage 7 million regionally-based Eagles fans, not just the 70,000 fans who would witness Dawkins' retirement ceremony inside Lincoln Financial Field during the game. This case illustrates how the partners came together to achieve common goals, using Dawkins' image, presence, and positive affinity with Eagles fans. The case details sponsorship and activation trends, the activation ratio, and other examples of sponsorship activation tied to athlete retirement. The case asks students to take what they have learned about sponsorship activation and analyze the Dawkins retirement, discussing what was successful, what was not, and what could be done for future sponsorship activations in similar situations.
Originally published in Pasqualicchio, G., O'Reilly, N., & Elowson, E. (2017). From 70 thousand to 7 million: Integrated activation as a driver of sponsor and property reach. Case Studies in Sport Management, 6(1), 1-9. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Philadelphia Eagles (Football team) -- Case studies; Corporate sponsorship -- United States -- Case studies; Sports sponsorship -- United States -- Case studies